Sensory and Quality Evaluation of Mayonnaise and its Effect on Storage Stability - Pradhananga, Mahalaxmi; Adhikari, Babita (Sunsari Technical College Journal, 2016)
This study aimed to evaluate the addition of skim milk powder to replace egg yolk in preparation of mayonnaise. Egg yolk was pasteurized at 150ºF (65.6ºC) about 1 minute for its safety. Mayonnaise was prepared from sunflower oil with the level varied from 65-75% and egg yolk from 9-15%. Mayonnaise made from 70% oil and 12% egg yolk was found to be best. Then skim milk powder (SMP) was added to replace 12% egg yolk in the ratios 0:100, 25:75, 50:50, 75:25 and 100:0 other constituents remaining constant. Sensory evaluation demonstrated that mayonnaise substituted with 25% skim milk powder was best. The chemical composition of the product, as well as fatty acid composition and peroxide value was analyzed. Coliform and Salmonella was not detected in microbial analysis. Sensory studies for its storage stability confirmed that the product was acceptable up to 28th days at refrigerate temperature whereas sample stored in room temperature was deteriorated after 14th days. Sunsari Technical College Journal 2015, 2(1):48-53